2019
DOI: 10.1182/bloodadvances.2018030577
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD47 in Sézary syndrome with SIRPαFc

Abstract: Sézary syndrome (SS), the leukemic variant of cutaneous T-cell lymphoma, has limited treatment options and rare occurrences of long-term remission, thus warranting research into new treatment approaches. CD47 has emerged as a promising target for multiple tumor types, but its role in SS remains unknown. Here, we show that CD47 is highly expressed on Sézary cells in the peripheral blood and skin, and the high level of CD47 expression correlates with worse overall survival (OS) in patients with SS. We also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 52 publications
(53 reference statements)
0
65
0
Order By: Relevance
“…After single-dose infusion of TTI-621, 4 of 5 patients had a decrease in their count and a rapid decrease of lactate dehydrogenase (LDH). Additional experiments showed that SIRPαFc increased the phagocytosis of ex vivo Sezary cells extracted from patient blood, but not non-malignant lymphocytes [36].…”
Section: Targeting Of Cd47-sirpα Using Antibodiesmentioning
confidence: 95%
See 1 more Smart Citation
“…After single-dose infusion of TTI-621, 4 of 5 patients had a decrease in their count and a rapid decrease of lactate dehydrogenase (LDH). Additional experiments showed that SIRPαFc increased the phagocytosis of ex vivo Sezary cells extracted from patient blood, but not non-malignant lymphocytes [36].…”
Section: Targeting Of Cd47-sirpα Using Antibodiesmentioning
confidence: 95%
“…Flow cytometry performed on 25 patients with Sezary syndrome (SS) showed higher CD47 expression in tumor cells compared with benign T-cells from the same individual. Patients with high expression of CD47 had 6.5 times shorter overall survival (OS) than patients with low expression (median OS, 84.0 vs 12.9 months; P < .001) [36].…”
Section: Role Of Cd47 In Nhlmentioning
confidence: 99%
“…Another approach of immunogenic cell death induction is to exploit the interaction of CD47 with its ligand signal regulatory protein α (SiRPα). By targeting tumor-cell CD47 through a decoy receptor (SiRPαFc), reverting the "do-noteat-me" signal to bystander macrophages, a significant reduction of tumor load was observed in various hematologic malignancies, i.e., CTCL [76]. Perturbation of NK-cell tolerance, e.g., by anti-KIR3DL2 antibodies, is a further strategy of proven activity in other T cell tumors [76,77].…”
Section: Modulation Of Immune Cell Synapsesmentioning
confidence: 99%
“…Nevertheless, clinically proven GvL effects [48] and TCRdirected CAR-T cells in pre-clinical models [79••] implicate a therapeutic application of a T cell-mediated anti-T-PLL attack. Modulation of immune regulatory synapses, e.g., by perturbation of NK-cell tolerance (e.g., anti-KIR3DL2) or of macrophage inertia (e.g., SIRPαFc binding to CD47) represent interventional strategies of proven activity in other T cell tumors [76,77], which have yet to be evaluated for their efficacy in T-PLL anti-CDR3 CAR-T cells have not been reported in T-PLL [80].…”
Section: Outlook For Car-t Cell Therapymentioning
confidence: 99%
“…As part of a phase 1a trial, five patients with Sezary syndrome, the leukemic variant of cutaneous T-cell lymphoma were treated with TTI-621. Treatment resulted in significant tumor load reduction and skin improvement [98]. Overall, the use of CD47-targeting therapies in clinical settings has an exciting outlook and more comprehensive analysis of its effects on macrophages and other innate or adaptive immune cells needs to be conducted.…”
Section: New Macrophage-targeting Therapies In Hematologic Malignanciesmentioning
confidence: 99%